A new estimator of resolved molecular gas in nearby galaxies. Issue 1 (24th October 2020) - Chown, Ryan; Li, Cheng; Parker, Laura; Wilson, Christine D; Li, Niu; Gao, Yang
ABSTRACT: A relationship between dust-reprocessed light from recent star formation and the amount of star-forming gas in a galaxy produces a correlation between Wide-field Infrared Survey Explorer ( WISE ) 12 μ m emission and CO line emission. Here, we explore this correlation on kiloparsec scales with CO(1–0) maps from EDGE–CALIFA matched in resolution to WISE 12 μ m images. We find strong CO-12 μ m correlations within each galaxy and we show that the scatter in the global CO-12 μ m correlation is largely driven by differences from galaxy to galaxy. The correlation is stronger than that between star formation rate and H2 surface densities [Σ(H2 )]. We explore multivariable regression to predict Σ(H2 ) in star-forming pixels using the WISE 12 μ m data combined with global and resolved galaxy properties, and provide the fit parameters for the best estimators. We find that Σ(H2 ) estimators that include Σ (12\:μ m) are able to predict Σ(H2 ) more accurately than estimators that include resolved optical properties instead of Σ (12\:μ m) . These results suggest that 12 μ m emission and H2 as traced by CO emission are physically connected at kiloparsec scales. This may be due to a connection between polycyclic aromatic hydrocarbon emission and the presence of H2 . The best single-property estimator is Σ (H_2)M_\:pc^-2 = (0.48 ± 0.01) + (0.71 ± 0.01)Σ (12\:μ m)L_\:pc^-2 . This correlation can be used to efficiently estimate Σ(H2 ) down to at least 1 M⊙ pc −2 in star-forming regions within nearby galaxies.